Prevalence of Mycobacterium bovis in deer in mainland China: a systematic review and meta-analysis - Li, Dong; Li, Dan-Ni; Liu, Xin-Yue; Song, Yu-Hao; Liu, Xue-Tong; Sehrish, Siddique; Jia, Yu-Xin; Zong, Ying; Li, Jian-Ming; Shi, Kun; Leng, Xue; Liu, Fei; et al. (Frontiers in Veterinary Science, 2024)
Deer tuberculosis is a chronic zoonotic infectious disease, despite the existence of socio-economic and zoonotic risk factors, but at present, there has been no systematic review of deer tuberculosis prevalence in mainland China. The aim of this meta-analysis was to estimate the overall prevalence of deer TB in mainland China and to assess possible associations between potential risk factors and the prevalence of deer tuberculosis.This study was searched in six databases in Chinese and English respectively (1981 to December 2023). Four authors independently reviewed the titles and abstracts of all retrieved articles to establish the inclusion exclusion criteria. Using the meta-analysis package estimated the combined effects. Cochran's Q-statistic was used to analyze heterogeneity. Funnel plots (symmetry) and used the Egger's test identifying publication bias. Trim-and-fill analysis methods were used for validation and sensitivity analysis. we also performed subgroup and metaregression analyses.In this study, we obtained 4400 studies, 20 cross-sectional studies were screened and conducted a systematic review and meta-analysis. Results show: The overall prevalence of tuberculosis in deer in mainland China was 16.1% (95% confidence interval (CI):10.5 24.6; (Deer tuberculosis infected 5367 out of 22215 deer in mainland China) 5367/22215; 1981 to 2023). The prevalence in Central China was the highest 17.5% (95% CI:14.0-21.9; 63/362), and among provinces, the prevalence in Heilongjiang was the highest at 26.5% (95% CI:13.2-53.0; 1557/4291). Elaphurus davidianus was the most commonly infected species, with a prevalence of 35.3% (95% CI:18.5-67.2; 6/17). We also assessed the association between geographic risk factors and the incidence of deer tuberculosis.Deer tuberculosis is still present in some areas of China. Assessing the association between risk factors and the prevalence of deer tuberculosis showed that reasonable and scientific-based breeding methods, a suitable breeding environment, and rapid and accurate detection methods could effectively reduce the prevalence of deer tuberculosis. In addition, in the management and operation of the breeding base, improving the scientific feed nutrition standards and establishing comprehensive standards for disease prevention, immunization, quarantine, treatment, and disinfection according to the breeding varieties and scale, are suggested as ways to reduce the prevalence of deer tuberculosis.